Diagnostic Value of Gd‐EOB‐DTPA‐Enhanced MRI for the Expression of Ki67 and Microvascular Density in Hepatocellular Carcinoma. Issue 6 (1st November 2019) - Chen, Yidi; Qin, Xiali; Long, Liling; Zhang, Ling; Huang, Zhongkui; Jiang, Zijian; Li, Chenhui
Abstract : Contract grant sponsor: National Natural Science Foundation of China; Contract grant number: 81260214. Background: Recent studies have highlighted the diagnostic value of Gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid (Gd‐EOB‐DTPA)‐enhanced MRI in small hepatocellular carcinoma (HCC). Ki67 and CD34 are histologic markers that reflect the proliferation of tumor cells and the microvascular density (MVD). Purpose: To explore the diagnostic value of Gd‐EOB‐DTPA‐enhanced MRI for Ki67 expression and MVD in HCC. Study Type: Retrospective. Subjects: In all, 180 patients with HCC. Field Strength/Sequence: 3.0T, Gd‐EOB‐DTPA‐enhanced T1 WI volumetric interpolated breath‐hold examination (VIBE) axial fat suppression plain, and enhanced scanning. Assessment: The T1 relaxation time (T1 rt) and signal intensity (SI) of the lesion were measured. The Ki67 expressions and MVD were evaluated by immunohistochemistry. Statistical Test: Receiver operating characteristic (ROC) curves were used to analyze the diagnostic efficacy of T1 rt for high Ki67 expression (≥50%) and high MVD (≥100). Results: The T1 rt‐20min, rrT1 rt‐20min, and SI‐hepatobiliary phase (SI‐HBP) were strongly correlated with Ki67, the r values were 0.846, –0.765, and –0.760 ( P < 0.05), respectively. There were moderate correlations with CD34, with r values –0.444, 0.336, and –0.463 ( P < 0.05), respectively. The T1 rt‐Pre, T1 rt‐20min, SI‐Pre, and SI‐HBP were significantly different both between the high and low ki67 expression groups ( P < 0.05) and between the high MVD and low MVD groups ( P < 0.05). In the two groups the T1 rt‐20min and SI‐HBP was 800.06 ± 128.91 vs. 530.06 ± 139.29 ( P < 0.05) and 122.29 ± 39.39 vs. 173.49 ± 46.15 ( P < 0.05); T1 rt‐20min was found to have high diagnostic efficiency for high ki67 expression (area under the curve [AUC], 0.937; P < 0.05) T1 rt‐20min had moderate diagnostic value for high MVD (AUC, 0.716; P < 0.05). Data Conclusion: The T1 rt and SI of Gd‐EOB‐DTPA‐enhanced MRI were correlated with Ki67 expression and MVD. T1 rt‐20min has a high diagnostic value for high ki67 expression and high MVD in HCC tissues. Level of Evidence : 3 Technical Efficacy Stage : 2 J. Magn. Reson. Imaging 2020;51:1755–1763.